Slametan sebagai Simbol Harmoni dalam Interaksi Sosial Agama dan Budaya Masyarakat Desa Tanon Kecamatan Papar Kabupaten Kediri - Hanik, Umi; Turmudi, Moh. (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2020)
This article was written with the aim to describe the interaction of religion and culture that occurred in the people of Tanon Village, Papar District, Kediri Regency, East Java. The issue of tolerance between religious communities will always be interesting to discuss, this is because religion is often a source of conflict. A pluralist and inclusive attitude becomes the social capital of the people to live in harmony. This study uses a qualitative method with a phenomenological approach. In-depth interviews became the main technique in collecting data and then analyzed using the Haberman and Milles flow techniques. The results showed that the social interactions developed by the Tanon villagers were able to create harmony in the life between religious communities